1996
DOI: 10.1097/00005176-199612000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal Reflux in Infants: Evaluation of a New Intraluminal Impedance Technique

Abstract: In this study, pH metry was simultaneously applied with a new technique, the intraluminal multiple electrical impedance (IMP) procedure, for measuring gastrointestinal motility for gastroesophageal reflux (GER) detection. Seventeen infants with clinical symptoms of GER disease such as recurrent apnea, aspiration pneumonia, wheezing, and failure to thrive were investigated during two feeding periods. A single catheter combining a pH electrode with seven electrodes for impedance measurements over a distance of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
142
0
4

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 23 publications
5
142
0
4
Order By: Relevance
“…The combined impedance and pH catheter technique can record all types of reflux episodes, i.e., air, liquid, acid, and neutral (16,18,19,(22)(23)(24)(25). The technique is based on the measurement of electrical impedance between closely spaced electrodes positioned in the esophagus.…”
mentioning
confidence: 99%
“…The combined impedance and pH catheter technique can record all types of reflux episodes, i.e., air, liquid, acid, and neutral (16,18,19,(22)(23)(24)(25). The technique is based on the measurement of electrical impedance between closely spaced electrodes positioned in the esophagus.…”
mentioning
confidence: 99%
“…14 Impedance has been proposed as a non-radiological tool for studying oesophageal volume clearance after reflux 15 but specific validation studies are not available.…”
mentioning
confidence: 99%
“…The commonly used tests such as videofluoroscopic swallowing studies and radionuclide scintigraphy have been found to be quite insensitive (5). Gastroesophageal reflux can be diagnosed by using these techniques and also by 24-h esophageal pH monitoring (17), echo-Doppler ultrasound (18), and esophageal intraluminal impedance (19). However, these tests are of no use in diagnosing aspiration.…”
Section: Discussionmentioning
confidence: 99%